The effectiveness of pediatric obesity prevention policies: a comprehensive systematic review and dose–response meta-analysis of controlled clinical trials - Taghizadeh, Shahnaz (J Transl Med, 2020)
BACKGROUND: Childhood obesity persists as a serious public health problem. In the current meta-analysis, we summarized the results of controlled trials that evaluated the effect of obesity prevention policies in children and adolescents. METHODS: Three databases (SCOPUS, PubMed and Embase) were searched for studies published before the 6th April 2020, by reported outcome measures of body mass index (BMI) and BMI-Z(score). Forty-seven studies reported BMI, while 45 studies reported BMI-Z(score) as final outcome. RESULTS: The results showed that the obesity-prevention policies had significant effect in reducing BMI (WMD: − 0.127; CI − 0.198, − 0.056; P < 0.001). These changes were not significant for BMI-Z(score) (WMD: − 0.020; CI − 0.061, 0.021; P = 0.340). In dose–response meta-analysis, a non-linear association was reported between the duration of intervention and BMI (P(nonlinearity) < 0.001) as well as BMI-Z(score) (P(nonlinearity) = 0.023). In subgroup analysis, the more favorite results were observed for 5–10 years old, with combination of physical activity and diet as intervention materials. CONCLUSION: In conclusion, the obesity prevention policies in short-term periods of less than 2 years, in rather early age of school with approaches of change in both of diet and physical activity, could be more effective in prevention of childhood obesity. Trial registration PROSPERO registration number: CRD42019138359